2021
DOI: 10.3748/wjg.v27.i40.6951
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and gastrointestinal disturbances in Egyptian patients infected with coronavirus disease 2019: A multicentre cohort study

Abstract: BACKGROUND Various liver and gastrointestinal involvements occur in patients with coronavirus disease 2019 (COVID-19) at variable prevalence. Most studies report mild liver function disturbances correlated with COVID-19 severity, though liver failure is unusual. AIM To study liver and gastrointestinal dysfunctions in Egyptian patients with COVID-19 and their relation to disease outcomes METHODS This multicentre cohort study was conducted on 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
3
6
1
Order By: Relevance
“…Our study showed that the most common presentations of SARS-CoV-2 infection were fever (80%), cough (68.7%), and dyspnea (65%) which was consistent with previous studies [22][23][24]. Moreover, middle-aged, and elderly people were more susceptible to COVID-19, which may be contributed to the lower immunity in these populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that the most common presentations of SARS-CoV-2 infection were fever (80%), cough (68.7%), and dyspnea (65%) which was consistent with previous studies [22][23][24]. Moreover, middle-aged, and elderly people were more susceptible to COVID-19, which may be contributed to the lower immunity in these populations.…”
Section: Discussionsupporting
confidence: 91%
“…Within our cohort, 104 (34.7%) patients presented with GI symptoms which is lower than the results reported by other studies conducted in the USA and China which were in the range of 50.5-61.3% [10,12]. In contrast, this prevalence was higher than other studies conducted in China, Italy, and Egypt [7,22,24,25].…”
Section: Discussioncontrasting
confidence: 83%
“…In another study by Sarin et al [ 36 ], including 185 noncirrhotic patients with CLD and 43 cirrhotic patients, higher rates of severe liver injury and mortality were shown following COVID-19 disease, especially in patients with more decompensated liver disease (Child–Pugh score ≥ 9). Furthermore, some patients with cirrhosis may develop either acute-on-chronic liver failure (ACLF) or acute decompensation[ 37 ].…”
Section: Patients With Liver Cirrhosis and Covid-19mentioning
confidence: 99%
“…In addition, Shousha et al [ 35 ] conducted a prospective cohort study in 547 Egyptian patients with COVID-19 in order to investigate the underlying prevalence and severity of liver and gastrointestinal disturbances, as well as their effect on disease outcomes[ 35 ]. Among patients who required ICU admission (122/547), 48.50% had elevated AST and 35.60% had elevated ALT.…”
Section: Existing Evidencementioning
confidence: 99%
“…In the multivariate analysis, FIB-4 score > 3.25 was a significant predictor of mortality. Unfortunately, no other specific ICU details could be extrapolated from this study, owing to the trial design and aim, which was not focused on ICU patients[ 35 ].…”
Section: Existing Evidencementioning
confidence: 99%